Positive Solutions of nth-Order Nonlinear Impulsive Differential Equation with Nonlocal Boundary Conditions. (10th June 2010) - Feng, Meiqiang; Zhang, Xuemei; Yang, Xiaozhong
Abstract : This paper is devoted to study the existence, nonexistence, and multiplicity of positive solutions for then th-order nonlocal boundary value problem with impulse effects. The arguments are based upon fixed point theorems in a cone. An example is worked out to demonstrate the main results.